Expressions Creating Confusion among Elements of Promotion Mix: Sales Promotion - Dinmukhamed Kelesbayev; Kuatbek Kalykulov; Yermek Yertayev; Altynay Turlybekova; Akhmet Kamalov (International Review of Management and Marketing, 2017)
More than twenty years on marketing, research and publications have dealt with research problems based on marketing mix and have mostly examined marketing processes. However, the types or elements of the marketing mix that are important for both the enterprises and the consumers are not analyzed too deeply, and different expressions or concepts are used in the analyzed sources. For example, when we look at the literature on marketing, which is being used as a source in our universities, the conceptual confusion in the naming of the marketing mix components and elements of promotion mix is clearly visible. Marketing literatures are developed by academicians who contribute to the expansion and development of marketing literature, such as sales promotion or sales incentives or sales encouragement. The concepts that are placed as such are the concepts confusion in naming elements of promotion mix and the promotion mix. Therefore, in this study, a deep literature search was conducted to get rid of concept confusion. In the naming of elements of promotion mix, concept expressions that create confusion have been examined in detail and discussed in various comparative terms, and basic concepts with wide meaningful various actions have been proposed.